2011
DOI: 10.2334/josnusd.53.15
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic evaluation of subcutaneous tissue response to three endodontic sealers in rats

Abstract: The aim of this study was to evaluate the subcutaneous biocompatibility of three root canal sealers in rats. Thirty Wistar rats were divided into three groups according to three time periods (15, 30 and 60 days). Sterilized polyethylene tubes filled with root canal sealers (AH Plus, Epiphany & Grossman), and one empty tube (control) were implanted into four separate dorsal regions in each rat. At the end of each study period, 10 animals were sacrificed, and histologic sections of connective tissue at the open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
3
7
0
2
Order By: Relevance
“…The results showed minor inflammatory infiltration after 7 days, which then returned to normal after 30 days. The same observation was recorded by others (Farhad et al 2011, Parirokh et al 2011, and they reported a less severe or no inflammatory reaction of subcutaneous tissue to an implanted empty tube after 30 days. Olsson et al (1981) concluded that all dental materials have distinct irritability.…”
Section: Discussionsupporting
confidence: 83%
“…The results showed minor inflammatory infiltration after 7 days, which then returned to normal after 30 days. The same observation was recorded by others (Farhad et al 2011, Parirokh et al 2011, and they reported a less severe or no inflammatory reaction of subcutaneous tissue to an implanted empty tube after 30 days. Olsson et al (1981) concluded that all dental materials have distinct irritability.…”
Section: Discussionsupporting
confidence: 83%
“…60 or 90 days 9 . As regards the groups evaluated, zinc oxide presented the highest degrees of inflammatory infiltration, as has previously been observed, due its cytotoxicity 25 . Although this substance presented good results with respect to tissue repair, probably due to its anti-oxidant power, anti-inflammatory potential and tissue repair activity 26,27 .…”
Section: Discussionsupporting
confidence: 65%
“…Because of the physical limitations of core materials, sealers play an important role in root canal obturation, as they fill all voids and spaces within the tooth [2].…”
Section: Introductionmentioning
confidence: 99%